PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum L.) - Posundu, Altris Stevani; Ramli, Ramli (Fakultas Pertanian, Universitas Tadulako, 2024)
This study aimed to evaluate the effect of different growing media on the growth and yields of tomato plants (Solanum lycopersicum). The experiment was conducted at the Academic Farm of the Faculty of Agriculture, Tadulako University, Palu, Central Sulawesi, from March to May 2021. A Randomized Complete Block Design (RCBD) was employed with six different treatments: P0 (Control, soil only), P1 (Soil + Rice Husk Charcoal 1:1), P2 (Soil + Rice Husk Charcoal 1:2), P3 (Soil + Rice Husk Charcoal 1:3), P4 (Soil + Rice Husk Charcoal 3:1), and P5 (Soil + Rice Husk Charcoal 3:2). Each treatment was replicated four times, resulting in a total of 24 experimental units, with each unit containing three plants, amounting to a total of 72 plants per polybag. The results demonstrated that the P3 treatment (Soil + Rice Husk Charcoal 1:3) significantly enhanced the growth and yields of tomato plants. This treatment yielding the highest performance: an average plant height of 99.44 cm, 81.58 leaves, 12.78 branches, 11.56 fruits per plant, and an average fruit weight of 363.12 g. These findings suggest that the P3 growing medium is particularly effective in promoting the optimal growth and productivity of tomato plants.